Upregulation of iNOS contributes to attenuated cutaneous vasodilation in essential hypertensive humans - Smith, Caroline J. (2011)
Essential hypertension is a pro-inflammatory, pro-constrictor disease coinciding with endothelial dysfunction and inward vessel remodeling. Using the skin circulation our aim was to determine if iNOS upregulation attenuates NO-dependent cutaneous vasodilation in hypertensive humans. We hypothesized that with hypertension (1) localized iNOS inhibition would restore vasodilation in response to NO-dependent stimuli and (2) iNOS expression would be increased and phosphorylated vasodilator-stimulated phosphoprotein (pVASP) would be decreased. In vivo protocols: four intradermal microdialysis (MD) fibers were placed in 9 hypertensive and 10 normotensive (SBP: 146 ± 4 vs.113 ± 2 mmHg, p<0.001) men and women. MD fibers served as control, iNOS-inhibited (1400W), nNOS-inhibited (NPLA), and non-selective NOS-inhibited (L-NAME). Cutaneous vascular conductance was calculated (%CVC(max); sodium nitroprusside) during standardized local heating (42°C) and acetylcholine (ach) dose-response protocols (0.01, 0.1, 1, 5, 10, 50, 100 mmol/L). The NO-dependent local heating response was attenuated at control (95 ± 2 vs. 76 ± 2 %CVC(max), p<0.05) and nNOS-inhibited sites (94 ± 4 vs. 77 ± 3 %CVC(max), p<0.01) in hypertensives. iNOS inhibition augmented the NO-dependent local heating response (93 ± 2 vs. 89 ± 10 %CVC(max)). Ach-induced vasodilation was attenuated in control sites at doses ≥ 0.1mM Ach in hypertensives, and was restored with iNOS inhibition (0.1 mM p<0.05; 1, 5, 10 mM p<0.001; 50, 100 mM p<0.01). In vitro iNOS expression was increased (p=0.006) and pVASP/VASP was decreased in skin from hypertensive humans (p=0.04). These data suggest that iNOS is upregulated in essential hypertensive humans and contributes to reduced NO-dependent cutaneous vasodilation.